FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN CARPAL TUNNEL SYNDROME (CTS) PADA PEKERJA UNIT ASSEMBLING PT X KOTA SEMARANG TAHUN 2018 - Erlangga Rendra Wardana; Siswi Wijayanti; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2018)
Manufactur is one of the industrial sectors that creates products. Higher competition within the sector causes many employers demand their worker to be more productive. Work process that runs manually sometimes causes musculoskeletal disorders to the workers, including Carpal Tunnel Syndrome (CTS). The purpose of this study was to analyze the factors that are related to the incidence of CTS in Assembling workers at PT X Semarang City in 2018. This study was a quantitative observational analytic study with cross-sectional design. The independent variables of this study were age, length of work, Rheumatoid Arthritis, repetitive movement, and awkward posture of the worker’s wrist. The dependent variable of this study was the incidence of CTS among the workers. This study took all of the Assembling workers as a population, with the total sampling used as a sampling method. An interview using questionnaire, Tinel’s Sign, and Phalen’s Test were used to determine CTS among the workers. The data obtained were analyzed using chi square test to see the relationship between variables. The study results showed that 55,9% of the Assembling workers were suffered from CTS. The results of statistical tests stated that there were relationship between age (p = 0,001), length of work (p = 0,010), Rheumatoid Arthritis (p = 0,008), and repetitive movement (p = 0,042) with the incidence of CTS among the workers. While awkward posture of the wrist had no relationship with the incidence of CTS. PT X should conduct socialization to all workers regarding factors that can cause CTS and the impact it has.